2017
DOI: 10.1111/jfs.12380
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sprouting environment on the microbiota of sprouts

Abstract: Sprouts are popular for health conscious and vegetarian consumers; however, this produce item has been associated with frequent foodborne outbreaks. To understand the influence of the sprouting environment on the microbiota colonizing the sprout, microbial populations of both sprouting seeds and sprouts were characterized using terminal fragment length polymorphism analysis. The dominant microbial populations on mung bean, alfalfa, and broccoli seeds over the course of germination were compared to the microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Coliforms were more prevalent in tray (4.96 ± 1.44), cutting board (5.62 ± 0.59) and glove (4.30 ± 0.00) from farm A and basket (5.57 ± 0.49), cutting board (5.40 ± 0.93) and glove (4.82 ± 0.11) from B during summer season compared to all the other samples including water (< 2 log CFU/ml), agricultural materials (< 3 log CFU/ml). Corresponding to our findings, several studies have reported increased microbial levels in postharvest sprouts than in seeds [18,20]. The incidence of E. coli was significantly higher in the preharvest (50%) and postharvest (39%) sprouts and water samples (33%) from farms B and C. E. coli was detected in the basket (5%), glove (16%), and knife (11%) samples, while no E. coli were detected in the other samples.…”
Section: Assessment Of Coliforms and E Coli Contamination In Radish supporting
confidence: 87%
“…Coliforms were more prevalent in tray (4.96 ± 1.44), cutting board (5.62 ± 0.59) and glove (4.30 ± 0.00) from farm A and basket (5.57 ± 0.49), cutting board (5.40 ± 0.93) and glove (4.82 ± 0.11) from B during summer season compared to all the other samples including water (< 2 log CFU/ml), agricultural materials (< 3 log CFU/ml). Corresponding to our findings, several studies have reported increased microbial levels in postharvest sprouts than in seeds [18,20]. The incidence of E. coli was significantly higher in the preharvest (50%) and postharvest (39%) sprouts and water samples (33%) from farms B and C. E. coli was detected in the basket (5%), glove (16%), and knife (11%) samples, while no E. coli were detected in the other samples.…”
Section: Assessment Of Coliforms and E Coli Contamination In Radish supporting
confidence: 87%
“…The cereal germination technique has been recognized as a method to improve the nutritional quality of whole grains, due to the changes it causes in nutritional and physicochemical properties. Moreover, it has been found in the literature that grain germination leads to the development of changes in the structure of the microbiota by increasing the process of utilization of carbon and nitrogen sources by probiotic microorganisms ( Barret et al, 2015 , Landry et al, 2018 , Perri et al, 2020 ).…”
Section: Sprouts Of Different Seeds and Grainsmentioning
confidence: 99%